The Medical Library Association guide to managing health care libraries (Neal-Schuman Publishers, 2011)
Contents: Introduction: libraries in health care settings / Margaret Moylan Bandy and Rosalind Farnam Dudden -- The health care environment / Margaret Moylan Bandy and Barbara Jahn -- Topics in management / Jacqueline Donaldson Doyle and Kay E. Wellik -- Financial management / Mary Fran Prottsman -- Human resources management / Dixie A. Jones -- Evaluation and improvement management / Rosalind Farnam Dudden -- Collection planning management / Craig C. Haynes -- Collection technical management / Gretchen Hallerberg ... [et al.] -- Library space management / Elizabeth Connor -- On-site and web-based information services / Susan Lessick -- Educational services / Lisa K. Traditi -- Information practice / Michele Klein-Fedyshin -- Knowledge services / Lorri Zipperer -- Health information for patients and consumers / Michele Spatz -- Associated services / Hope Leman ... [et al.] -- Solo librarians / Jerry Carlson.